Typifications of names in south American species of gutierrezia (asteraceae, astereae) - Ratto, Francisco (2019)
During the course of the revision of the South American species of Gutierrezia, we have detected names that require typification. After the analysis of the protologues and the herbarium specimens, we designated eight lectotypes and one neotype for nine names of the Gutierrezia genus and we assigned the category of holotype to one specimen. A detailed discussion is provided for each case.